EVALUATING THE ENVIRONMENTAL IMPACTS OF INDONESIA’S ELECTRIC VEHICLE POLICY: ALIGNING WITH SUSTAINABILITY AND CONSERVATION PRINCIPLES - Hardiyan, Salwa Putri; Wibawa, Kadek Cahya Susila; Azhar, Muhamad; Gabriel, Jaewook Lee (Faculty of Law, Universitas Diponegoro, 2025)
This study analyzes the environmental implications of Indonesia’s Battery Electric Vehicle (BEV) policy, as outlined in Presidential Regulation No. 55 of 2019. The policy aims to reduce greenhouse gas (GHG) emissions and promote a transition to renewable energy within the transportation sector. While the BEV program has contributed to a reduction in GHG emissions, the research identifies several environmental concerns associated with the policy. These include the environmental damage caused by nickel mining, the reliance on coal-fired power plants for electricity generation, and the inadequate handling of battery waste. The study evaluates these issues through the lens of Indonesia's Environmental Protection and Management Law, emphasizing the principles of sustainability and conservation. The findings suggest that the current implementation of the BEV policy does not fully adhere to these principles, as it neglects the broader environmental impacts of nickel extraction, fossil energy dependence, and improper battery waste management. To enhance the policy's effectiveness and ensure alignment with sustainable practices, the research recommends revisions in key areas such as raw material sourcing, energy generation for electric vehicle charging, and waste management protocols. The study highlights the need for a comprehensive and environmentally conscious approach to achieve the long-term goals of reduced emissions and a cleaner transportation system.